Root Growth Response of Soybean Under Water Deficit - Achmad Fatchul Aziez; Agung Prasetyo; Paiman Paiman (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2022)
Roots are plant organs that function to absorb water and nutrients from the rhizosphere. If the soil is dry, the roots will be affected first. This study aims to know the response of soybean root to drought stress. This research was arranged in a randomized completely block design (RCBD) with two factors and three replications. The first factor was soil moisture content, which consisted of four levels, e.i., 100, 75, 50, and 25% field capacity. The second factor was the growth stage, which consisted of three kinds, e.i., the vegetative active, flowering time, and seed filling period. The results showed that the soil water content in below 75% field capacity decreased root length, root fresh weight, root dry weight, root volume, and increased shoot root ratio. The seed filling period was more sensitive to water deficiency than the active vegetative and flowering time. The study findings that soybean plants can grow well at 100% field capacity. The practical implication of planting soybeans use a soil moisture content of 100% field capacity.